Could Hemokinin-1 (HK-1) be a Novel Candidate Biomarker for Sarcoidosis? - Turan Akdağ; Celalettin Korkmaz (Genel Tıp Dergisi)
Aim: Sarcoidosis is a systemic inflammatory disease and characterized by the presence of non-caseating granulomas which may affect all organs in the body. Some studies suggest an association between peptides and sarcoidosis. The goal of the study was to investigate the biomarker values of serum hemokinin-1 (HK-1) and adropin levels in sarcoidosis and to assess their role in the disease course. Patients and Methods: The study was carried out in a university hospital between April 2021 and February 2022. Thirty-eight patients with diagnosed sarcoidosis (14 men and 24 women) and 38 healthy (14 men and 24 women) individuals were enrolled in the study. Demographic characteristics, age, gender, disease duration, and extrapulmonary involvement of the patients were enrolled. HK-1 and adropin levels were measured via the sandwich ELISA (enzyme linked immunosorbent assay) method. Results: HK-1 level was elevated in the sarcoidosis patients than in the healthy individuals, these differences were significant statistically (0.67±0.23 and 0.54±0.24 ng/ml, p=0.012). The serum levels of adropin were measured as 207.84±246.72 ng/L in the sarcoidosis patients group and 151.16±171.76 ng/L in the healthy individuals group. No significant differences were determined in terms of the adropin levels in the patient's group when compared to the healthy individuals group (p=0.076). Serum adropin were negatively correlated with BAL CD4+ levels (r=-,880 and p=0.002) and positively correlated with BAL CD8+ levels (r=,697 and p=0.037). Conclusions: At the study, it is determined that patients with sarcoidosis show significantly higher HK-1 levels than healthy controls, and HK-1 may be a useful non-invasive diagnostic biomarker for this disease. From the literature, serum HK-1 and adropin levels have not been investigated in sarcoidosis, yet. To clarify this topic, further and larger size studies are needed.